Adaptability of Medium-low Speed Maglev System in City (Suburban) Railway - DAI Nengyun; DENG Juanhong; DAI Jue; LI Hao; HOU Xikuai (Chengshi guidao jiaotong yanjiu, 2024)
Objective Addressing the current issues of relatively limited system choices, large engineering investment, and high proportion of underground lines, the adaptability of medium-low speed maglev lines in city (suburban) railway is analyzed, and diversified system choices are provided for city (suburban) railway development. Method The functional positioning of city (suburban) railway and the technical characteristics of medium-low speed maglev lines are introduced. Combining with the technical requirements of city (suburban) railway, a detailed comparative analysis is conducted between medium-low speed maglev lines and wheel-rail lines from aspects including line adaptability, maximum operational speed, environmental compatibility, transportation capacity adaptability, interoperability and resource sharing, comprehensive energy consumption, engineering investment. Result & Conclusion Research results show that medium-low speed maglev lines have unique advantages in adaptability, environmental compatibility, ride comfort, and engineering investment, hence highly suitable for city railway lines characterized by significant terrain variations, longer urban routes, relatively independent service areas, and moderate passenger traffic volume.